1793 N.H. Laws 464-65, An Act to Prevent the Keeping of Large Quantities of Gun-Powder in Private Houses in Portsmouth, and for Appointing a Keeper of the Magazine Belonging to Said Town. - (:unkn) unknown (General Publisher, 1793)
That if any person or persons, shall keep in any dwelling-house, store or other building on land, within the limits of said Portsmouth, except the magazine aforesaid, more than ten pounds of gun-powder at any one time, which ten pounds shall be kept in a tin canister, properly secured for the purpose, such person or persons shall forfeit the powder so kept to the firewards of said Portsmouth to be laid out by them in purchasing such utensils as they may judge proper for the extinguishing of the fire;
--
Keywords: GUN POWDER STORAGE